BRIDGING DIGITAL DIVIDE THROUGH E-LITERACY PROGRAMME: THE CASE OF AKSHAYA PROJECT IN KERALA - Ashitha M K (International Journal of Research and Analytical Reviews, 2018)
Digital divide is the difference between people who have access to information and communication technology and people who do not have access. Various initiatives have been implemented in India for bridging the digital divide. Akshaya project was initiated in Kerala for bridging the digital gap through e-literacy programme. This paper is an attempt to analyze e-literacy programmes offered to the citizen under akshaya project for bridging the digital divide in the state.